PELATIHAN MEMBUKA JALAN BISNIS INKLUSIF UNTUK KOMUNITAS LINGKAR SOSIAL (LINKSOS) MALANG - Joni Dwi Pribadi; Umi Khabibah; Halid Hasan; Abdullah Helmy; Rizka Rahmawati; Fahmi Muhammad Az Zuhri (P3M Politeknik Negeri Malang, 2026)
The inclusive disability community at LINKSOS in Lawang, Malang Regency, produces various handicrafts such as batik and scrap-fabric accessories but lacks digital marketing reach to expand their market. This community service program aims to empower these inclusive MSMEs through online marketing training using WhatsApp Business. The activity employed a Lesson Study approach (planning, action, monitoring & evaluation) involving 30 participants, predominantly deaf and mute individuals. Training was facilitated through visual materials, direct mentoring, and adaptive communication without sign language interpreters. Evaluation results showed significant improvements: 100% of participants understood the importance of digital marketing, 83% successfully managed business profiles, and 93% mastered automated messaging. Partner satisfaction was rated highly, particularly regarding team mentoring. Overall, WhatsApp Business proficiency increased from 16% to 90%, with 70% of participants achieving independent account management. The program demonstrates that inclusive training methods effectively enhance digital literacy and economic independence for disabled MSMEs, though sustained mentoring remains necessary for advanced feature optimization.